2007
DOI: 10.1042/bj20070761
|View full text |Cite
|
Sign up to set email alerts
|

The NHB1 (N-terminal homology box 1) sequence in transcription factor Nrf1 is required to anchor it to the endoplasmic reticulum and also to enable its asparagine-glycosylation

Abstract: Nrf1 (nuclear factor-erythroid 2 p45 subunit-related factor 1) is negatively controlled by its NTD (N-terminal domain) that lies between amino acids 1 and 124. This domain contains a leucine-rich sequence, called NHB1 (N-terminal homology box 1; residues 11-30), which tethers Nrf1 to the ER (endoplasmic reticulum). Electrophoresis resolved Nrf1 into two major bands of approx. 95 and 120 kDa. The 120-kDa Nrf1 form represents a glycosylated protein that was present exclusively in the ER and was converted into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
181
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(197 citation statements)
references
References 54 publications
15
181
1
Order By: Relevance
“…The function of Keap1 binding domains present in Nrf1 is currently unknown. It has been shown that the Nrf1 N terminus is an important functional regulatory element that anchors the transcription factor to the membrane (57). The above analysis supports the idea that the various functions for the Nrf family were present before multiple duplications in modern vertebrates.…”
Section: Vol 31 2011supporting
confidence: 73%
See 1 more Smart Citation
“…The function of Keap1 binding domains present in Nrf1 is currently unknown. It has been shown that the Nrf1 N terminus is an important functional regulatory element that anchors the transcription factor to the membrane (57). The above analysis supports the idea that the various functions for the Nrf family were present before multiple duplications in modern vertebrates.…”
Section: Vol 31 2011supporting
confidence: 73%
“…This classification is based on the ability of Cnc-C to promote transcription of antioxidant genes and the observation that Cnc-C can also be regulated by a homologous cytoplasmic binding repressor, Keap1, as found with the vertebrate Nrf2 transcription factor. The vertebrate Nrf1 transcription factor also has Keap1 binding domains; however, (38,57) and anchor the proteins to membranes. The Drosophila Cnc-C N terminus shows similarities to both mammalian Nrf1 and Nrf2 critical domains.…”
Section: Inhibition Of Ubmentioning
confidence: 99%
“…Thus glycosylation may direct the intracellular transport or regulates the activation of TCF11. 46,58 Zhang and colleagues discuss a cleavage-independent mechanism, requiring an importin (KPNA4-16)-mediated translocation of TCF11 in a membranebound state.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…46,57,58 This process requires the p97-mediated extraction from the membrane and the ubiquitylation by the ER-resident E3-ubiquitin-ligase HRD1. In response to proteasome inhibition TCF11 is translocated from the ER to the nucleus, where it dimerizes with other bZIP-TFs and transactivates the transcription of UPS-genes (Fig.…”
Section: Tcf11 Activation Via Regulated Intramembrane Proteolysis (Rip)mentioning
confidence: 99%
See 1 more Smart Citation